Pengaruh Hemolisis Terdapat Kadar Serum Glutamate Pyruvate Transaminase (SGPT) Sebagai Salah Satu Parameter Fungsi Hati - hartono kahar (Universitas Muhammadiyah Surabaya, 2017)
AbstractSGPT examination is one of the important checks on the state of a particular patient, for example, in patients with liver disease, hepatitis, and so forth. The other purpose is to detect the presence of liver damage. So there was an effect in the event of an increase in maupaun drop in levels. And the serum circumstances that do not qualify, such as serum hemolysis, will greatly affect the actual levels of ALT. Based on the research background, the authors formulate the problem as follows: